A framework of Collaborative Commerce and internet organisation business model innovation in the tourism industry: the case study of the Veterans Affairs Commission in Taiwan. (1st January 2011) - Hsiang, Chin-Hsiao; Chen, Ruey-Shun; Chen, Y-C.; Chen, Chia-Chen
The purpose of this study is to improve the website linking access of the government's tourism information portal. Through the Extra-Web Organisation (EWO) framework of the cross-website operations, the collaborative commerce led to the top-down and bottom-up modelling can be achieved. In accordance with the characteristics of the tourism, it also addresses three different scales EWO business models and eight farms case of Veterans Affairs Commission in Taiwan to explore the draft framework and to verify the managerial effects for the collaborative operation. The result of this paper provides the government agencies with the references for the development of tourism organisation.